HSP60 reduction protects against diet-induced obesity by modulating energy metabolism in adipose tissue - Robert Hauffe; Michaela Rath; Mareike Schell; Katrin Ritter; Kai Kappert; Stefanie Deubel; Christiane Ott; Markus Jähnert; Wenke Jonas; Annette Schürmann; André Kleinridders (Elsevier, 2021)
Objective: Insulin regulates mitochondrial function, thereby propagating an efficient metabolism. Conversely, diabetes and insulin resistance are linked to mitochondrial dysfunction with a decreased expression of the mitochondrial chaperone HSP60. The aim of this investigation was to determine the effect of a reduced HSP60 expression on the development of obesity and insulin resistance. Methods: Control and heterozygous whole-body HSP60 knockout (Hsp60+/−) mice were fed a high-fat diet (HFD, 60% calories from fat) for 16 weeks and subjected to extensive metabolic phenotyping. To understand the effect of HSP60 on white adipose tissue, microarray analysis of gonadal WAT was performed, ex vivo experiments were performed, and a lentiviral knockdown of HSP60 in 3T3-L1 cells was conducted to gain detailed insights into the effect of reduced HSP60 levels on adipocyte homeostasis. Results: Male Hsp60+/− mice exhibited lower body weight with lower fat mass. These mice exhibited improved insulin sensitivity compared to control, as assessed by Matsuda Index and HOMA-IR. Accordingly, insulin levels were significantly reduced in Hsp60+/− mice in a glucose tolerance test. However, Hsp60+/− mice exhibited an altered adipose tissue metabolism with elevated insulin-independent glucose uptake, adipocyte hyperplasia in the presence of mitochondrial dysfunction, altered autophagy, and local insulin resistance. Conclusions: We discovered that the reduction of HSP60 in mice predominantly affects adipose tissue homeostasis, leading to beneficial alterations in body weight, body composition, and adipocyte morphology, albeit exhibiting local insulin resistance.